Chemical Modifications of Pyridoxine for Biological Applications: An Overview - Pawar, Rajashree; Chaudhran, Preeti; Pandey, Dheeraj; Sharma, Abha (Current Topics in Medicinal Chemistry, 2023)
Pyridoxine and its derivatives, pyridoxamine, and pyridoxal have been recognized for more than 70 years and are known for regulating cellular biology and metabolism. During the past few decades, the anti-oxidant and anti-inflammatory properties of pyridoxine and its vitamers were explored. However, an interesting turnabout was observed in pyridoxine chemical modification in the last two decades. The various important pathophysiological aspects of pyridoxine and its derivatives on several cellular systems have been discovered by researchers. Recent findings have shown that many diseases, like cancer, diabetes, hypertension, tuberculosis, epilepsy, and neurodegenerative diseases are linked to the alteration of pyridoxine. Herein, our main focus is to review the importance of pyridoxine and its derivatives obtained by various chemical modifications, in various disease areas and to recognize important directions for future research.
Keywords: Pyridoxamine